Value-Based Leadership Integration In Educational Management And Role In Sustaining Institutional Innovation - Nur Efendi (International Journal of Education Management and Religion, 2025)
This study investigates the integration of value-based leadership in educational management and its role in sustaining institutional innovation at Madrasah Aliyah Aswaja Ngunut. The research addresses how leadership grounded in ethical values is enacted, how it supports management processes, and how it contributes to innovation sustainability. A qualitative case study design was employed to capture in-depth perspectives from the principal, teachers, and administrative staff. Data were collected through semi-structured interviews, observations, and document analysis, followed by thematic analysis. The findings reveal that value-based leadership is embedded in participatory decision-making, transparent communication, and consistent policy implementation, which strengthen trust and professional engagement. Educational management operates through collaborative planning, reflective practice, and continuous evaluation, enabling adaptive and responsive institutional processes. Innovation is sustained through the alignment between leadership values, management practices, and instructional implementation. The study also identifies a cyclical relationship in which leadership guides management, management facilitates innovation, and innovation outcomes inform leadership refinement. These findings underscore the importance of integrating value-based leadership to sustain innovation in Islamic educational institutions.